Life-Threatening Necrotizing Fasciitis of the Posterior Neck - Ji-An Choi; Jung-Ha Kwak; Chung-Min Yoon (Journal of Trauma and Injury)
Necrotizing fasciitis is an infection of the subcutaneous tissue that results in destruction of the fascia and is disproportionately common in patients with chronic liver disease or diabetes. Necrotizing fasciitis of the head and neck is rare, but has a high fatality rate. A 50-year-old man with a past medical history of diabetes reported a chief complaint of a wound in the posterior neck due to trauma. The wound had grown and was accompanied by pus and redness, and the patient had a fever. When the patient was referred to department of plastic & reconstructive surgery, the sternocleidomastoid muscle, semispinalis capitis muscle, splenius capitis muscle, and trapezius muscles were exposed, and the size of the defect was about 25×20 cm. Dead tissue resection was performed before negative-pressure wound therapy, followed by a split-thickness skin graft (STSG). After a 2-week course of aseptic dressing post-STSG, the patient recovered completely. No postoperative complications were observed for 1 year. Necrotizing fasciitis is a life-threatening, rapidly spreading infection, requiring early diagnosis and active surgical treatment. In addition, broad-spectrum antibiotics are required due to the variety of types of causative bacteria. Broad necrotizing fasciitis of the posterior neck is rare, but can quickly progress into a life-threatening stage.